Pemanfaatan Media Sosial dalam Membangun Brand Image Lembaga Dakwah Kampus Al-Izzah UINSU - Awaluddin Siregar; Abdul Rasyid (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This journal aims to analyze the role and impact of using social media in building the brand image of the UINSU Al-Izzah Campus Da'wah Institute. In today's digital era, social media has become an important platform for organizational communication and promotion. UINSU's Al-Izzah Campus Da'wah Institute as an institution engaged in the field of da'wah on campus has the need to build a strong brand image to attract the interest of students and the wider community. This study used a qualitative method by collecting data through literature studies and interviews with members of the UINSU Al-Izzah Campus Da'wah Institute and campus social media managers. In addition to the benefits, this research also identifies some of the challenges faced in using social media to build brand image. These challenges include difficulties in reaching the right audience, obtaining active participation from followers, and maintaining the consistency and integrity of da'wah messages on social media. Therefore, this journal also discusses strategies for UINSU's Al-Izzah Campus Da'wah Institute in utilizing social media effectively, such as compiling relevant content, optimizing the use of hashtags, and holding interactive programs that involve followers. Keywords: Social Media, Brand Image, Building campus reputation, Al-Izzah campus da'wah institute, Uinsu.